Actinomyces europaeus as an emerging cause of necrotizing fasciitis. (2023) - Anthony, Nathan; Douthit, Nathan T.; Foster, Allen
Abstract: Necrotizing fasciitis is a type of necrotizing soft tissue infection (NSTI) that can be polymicrobial or monomicrobial in origin. Polymicrobial infections typically involve anaerobes of the Clostridium or Bacteroides family. This case report highlights necrotizing fasciitis caused by an unusual culprit, Actinomyces europaeus, which is a gram-positive anaerobic filamentous bacillus that has only been documented in one prior report to cause NSTI. Currently, about half of the hospitals in the United States are equipped to perform antibiotic susceptibility testing for anaerobes, but less than one-quarter of hospitals actually utilize these tests routinely. Thus, it is common for polymicrobial actinomycoses to be blindly treated with antibiotics that are beta-lactamase resistant and active against anaerobes, such as with piperacillin-tazobactam. Here we examine the potential impact of this lack of testing, as well as the evolution of A. europaeus to cause necrotizing fasciitis. Highlights: Actinomyces europaeus is among the most antibiotic resistant species of its genera. A. europaeus is evolving to cause necrotizing soft tissue infections. Hospitals in the USA do not commonly test anaerobes for antibiotic susceptibility. Reformation of treatment may be needed for Actinomycosis in the future.